COMPARATIVE STUDIES BETWEEN ALUM SYNTHESIZED FROM ALUMINUM CANS AND NATURAL COAGULANT SYNTHESIZED FROM WATERMELON SEED - SULAIMAN RAHAMA, Muhammad; LAWAL MASHI, Ahmed; ABUBAKAR, Sani Muhammad (Studia Universitatis Babeș-Bolyai Chemia, 2020)
This study focused on the comparative analyses between the alum synthesized from aluminum can and natural coagulant synthesized from watermelon seed in water treatment. It also involved the identification of phytochemical groups of watermelon seed cake. The two different synthesized coagulants were used in jar test analysis; the result obtained showed a good elimination of turbidity and suspended solid particles. The pH of the natural coagulant of the treated water falls within the range of 6.9 to 7.2. Alkaloid tannins, saponin, anthracene and flavonoid were found present in the watermelon seed cake. Moreover, the result from the research showed that both the natural coagulant synthesized from watermelon seed and the one synthesized from aluminum cans could be used as good flocculant in surface water treatment.